PENGARUH MOTIVASI BELAJAR DALAM PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 TERHADAP HASIL BELAJAR MATA PELAJARAN GEOGRAFI - Wiwi Permata Putri; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to determine the effect of learning motivation in online learning of geography in class X students of social science at SMA N 3 Padang. This research is a quantitative descriptive study, the research subjects are students of class X IPS in the Geography subject of SMA Negeri 3 Padang. The instrument used was a questionnaire, compiled using google form and distributed into the class WhatsApp Group application. The sampling technique used was saturated sampling, the number of respondents was 79 students. The results of this study are that there is a significant influence between learning motivation on student learning outcomes of class X SMAN 3 Padang with a value of r count = 0.299> r table = 0.221 and the value of tcount = 2.752> t table = 1.664.